A fatal case of melioidosis with pancytopenia in a traveler from Indonesia. Issue 4 (April 2017) - Katanami, Yuichi; Kutsuna, Satoshi; Horino, Atsuko; Hashimoto, Takehiro; Mutoh, Yoshikazu; Yamamoto, Kei; Takeshita, Nozomi; Hayakawa, Kayoko; Kanagawa, Shuzo; Kato, Yasuyuki; Ohmagari, Norio
Abstract: Melioidosis, an infectious disease with high mortality, caused by Burkholderia pseudomallei, is endemic in southeast Asia and northern Australia. In Indonesia, autochthonous cases have been rarely reported, with most cases being sporadic and occurring in travelers. Herein, we report a fatal case of neurological melioidosis in a traveler from Indonesia presenting with septic shock.